Myth and Migration: Unpicking the Career of the Reverend John Sprott - Murison, Barbara C. (Acadiensis, 2009)
The Scots appear to possess a particular flair for the creation, transmission, and mutation of myths, and while modern scholars have attempted to deconstruct such myths it is clear that they have been of substantial importance in the making of local and national identities. This article uses one Scottish emigrant to Nova Scotia as a test case. It unpicks the Galloway background of the Reverend John Sprott’s first four decades and the assembling of his cultural baggage, and it follows him for 50 years in his adopted homeland. A map of his mental journeyings is the result. Résumé Les Écossais semblent particulièrement doués pour la création, la transmission et la transformation de mythes. Bien que des chercheurs modernes aient tenté de déconstruire de tels mythes, ceux-ci ont manifestement été d’une importance considérable dans la construction d’identités locales et nationales. Cet article examine la vie d’un émigrant écossais en Nouvelle-Écosse comme un cas type. Il décortique les quatre premières décennies du révérend John Sprott passées en Galloway et la formation de son bagage culturel, et il le suit pendant 50 ans dans son pays d’adoption. Le résultat est une carte de son parcours mental.